Serum 25-Hydroxyvitamin D Levels as a Predictive Factor for Allergic Rhinitis - Restimulia, Lia; Munir, Delfitri (Sumatera Medical Journal, 2021)
Introduction: Allergy and 25-Hydroxyvitamin D deficiency were mentioned to be correlated. Still, there was limited number of studies in determining serum 25-Hydroxyvitamin D levels as a predictive factor, particularly in allergic rhinitis (AR). This study has never been implemented in Indonesia which the main objective was to explore this topic. Methods: Consecutive sampling was used in recruiting the fifteen subjects. Serum 25-Hydroxyvitamin D levels were quantified using electrochemiluminescence immunoassay (ECLIA) method while the total nasal symptom scores were acquired by enumerate all nasal symptoms. Data of serum vitamin D levels and TNSS were analysed statistically.Results: Based on our previous study, the predictive value was illustrated from linier regresion = 10,230 – 0,281 (vitamin D), with negative moderate correlation (r = -0,613). This result can be comparable for someone with vitamin D level of 5.66 ng/mL that could predicted as 8.64 nasal score. Conclusion: 25-Hydroxyvitamin D could be a predictive factor for allergic rhinitis with negative moderate correlation. Hence, in the future research needs to be implemented.